Akan Kasadwini (Akan Oral Literature) - Agyekum, K. (Dwumfour Publishers, 2011)
The book is a pioneering work of Akan oral literature written in the Akan language. It gives a theoretical view of oral literature and a detailed account of the major genres of oral literature in Akan. It deals with an introduction to literature and some aspects of stylistics. It ushers students of literature into some of the crucial issues of literature. The book deals with what literature is, and what it can afford to individuals and the society as a whole. It considers literature as an indispensable aspect of any society’s life. It also identifies the main characteristics of literature with specific reference to oral literature. The book treats some of the major terms in literature and supports them with examples. The book has 24 chapters and each chapter’s addresses, performance, composition, structure, functions and literary devices. Each chapter ends with sample questions that will help- students to revise what they have learned from the chapter. The book is in response to the needs of students at the WASSCE, Diploma and Degree levels to the subject matter of oral literature in Akan This book will also help Training College students both in their course work at college and also in their teaching.
Keywords: Oral literature; proverbs; folk tales; performance; composition; memorisation; elegy; surrogate language